2007
DOI: 10.1093/bja/aem039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol vs sevoflurane on arterial oxygenation during one-lung ventilation

Abstract: Background. The inhibitory effect of anaesthetic agents on hypoxic pulmonary vasoconstriction may depend upon their dose, especially when using a volatile agent. The aim of this randomized open study was to compare the effects of sevoflurane and propofol, as primary anaesthetic agents, on oxygenation during one-lung ventilation (OLV), with their administration being adjusted to maintain bispectral index (BIS) values between 40 and 60.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 33 publications
4
25
1
Order By: Relevance
“…The values of PaO 2 , SaO 2 , PvO 2 , SvO 2 , and CvO 2 in H group at both OLVþ30 and OLVþ60 were significantly higher than those in C group (*P < 0.05, z P < 0.01, compared with C group). approaches the mixed venous oxygen tension (PvO 2 ) [11]. PvO 2 is the important factor that may modify the HPV response during OLV.…”
Section: Discussionmentioning
confidence: 99%
“…The values of PaO 2 , SaO 2 , PvO 2 , SvO 2 , and CvO 2 in H group at both OLVþ30 and OLVþ60 were significantly higher than those in C group (*P < 0.05, z P < 0.01, compared with C group). approaches the mixed venous oxygen tension (PvO 2 ) [11]. PvO 2 is the important factor that may modify the HPV response during OLV.…”
Section: Discussionmentioning
confidence: 99%
“…3 Dose-dependent inhibition of HPV has been shown with the older inhaled anesthetics (halothane, nitrous oxide) 4 but is less well documented with the newer agents (desflurane, sevoflurane). 6,7 Other factors affecting HPV include systemic and pulmonary vasodilators, acid/base imbalance, and variations in cardiac output. 3,4 Complications Hypoxemia In the early days of thoracic anesthesia, hypoxemia was encountered in as many as 40% of cases with a Carlens double-lumen tube and manual ventilation.…”
Section: Physiology Of Olvmentioning
confidence: 99%
“…The newer inhalation anesthetics, desflurane and sevoflurane, however, appear to have lesser effects on HPV and provide equivalent oxygenation compared with propofol at similar anesthetic depths. 7 Furthermore, inhalational anesthetics appear to be lung protective. With OLV, a pro-inflammatory reaction takes place, exhibited by increased cytokine levels in bronchoalveolar lavage samples in either lung.…”
Section: Maintenance Of Anesthesiamentioning
confidence: 99%
“…Volatile anesthetic agents are known to inhibit HPV; however, the impact is minimal at less than 1 MAC and negligible with newer agents [22]. A recent Cochrane review of intravenous versus inhalational anesthesia for OLV concluded that there was very little evidence from randomized controlled trials to suggest differences in patient outcomes between groups [23 • ].…”
Section: Oxygenation During One-lung Ventilationmentioning
confidence: 99%